CONSERVATIVE METHODS OF POSTPARTUM GENITAL PROLAPSE CORRECTION - Karimova Feruza Javdatovna; Saatova Hulkar Muzaffar qizi; Hujamberdiev Chingiz Mannapovich (Web of Journals Publishing, 2025)
Postpartum complications, such as vaginal wall prolapse and urinary incontinence, account for approximately 28-39% of gynecological diseases in women of reproductive age. This problem is further exacerbated by the fact that about one-third of these patients are women of reproductive age planning pregnancy. Additionally, with age, pelvic organ prolapse takes on a progressive nature, leading to functional disorders, severe physical and emotional suffering.The most common complaints in the early stages of pelvic organ prolapse include recurrent bleeding, involuntary urine leakage during coughing or straining, as well as sexual dysfunction. This significantly reduces the quality of life for women. Previously undiagnosed pelvic floor muscle injuries identified through 3D ultrasound logically correlated with the results of perineal examinations, which can be interpreted as a clinical sign of post-traumatic vaginal laxity. Insufficient closure of the labia appears to be a cause of vaginal dysplasia and was found in 56% of women. According to the survey results, 23 (46%) patients noted a "hissing" sound during sexual intercourse, while 41 (79%) reported urinary incontinence during straining, weak intermittent stream, or splashing of urine during urination. Functional testing allowed for the diagnosis of uncomplicated urinary incontinence in patients with postnatal vaginal wall laxity. Urodynamic studies showed increased urination in 35% of women and obstructive urination in 27% during uroflowmetry, indicating weakening of the urethral sphincter against the background of vaginal wall laxity.Thus, early forms of pelvic organ prolapse in women of reproductive age are associated with recurrent infectious-inflammatory complications, bacterial vaginitis, urinary incontinence, and sexual dysfunction, all of which reduce the quality of life for these patients. There is no such concept as "asymptomatic" vaginal wall laxity. Even though the early signs of this complication may be asymptomatic, they serve as a prognostic factor for severe disability in the future.
Keywords: Urinary incontinence, female enuresis, overactive urinary tract, comprehensive urodynamic study, uroflowmetry, genital prolapse, cystocele, rectocele.